PENERAPAN AKUNTANSI LINGKUNGAN PADA BADAN USAHA MILIK DESA UNTUK MEWUJUDKAN GREEN ACCOUNTING (STUDI KASUS PADA BADAN USAHA MILIK DESA “X”) - Rizky Wulandari; Dina Natasari; Ihda Arifin Faiz (Monex: Journal of Accounting Research, 2019)
Abstract Village Owned Enterprises (BUMDes) is one of the village entities which foundation aims to improve village welfare through the optimization of village resources. BUMDes in its operations is expected to show social responsibility to the community. One of the social responsibilities is to apply environmental accounting. Environmental accounting means that accounting as a source of management's responsibility information to stakeholders which also provide information about the impact of business processes entity to the surrounding environment. Information on the environmental impacts disclosed in the financial statements which are referred to as Green Accounting. This research aims to analyze the application of environmental accounting on BUMDes "X" in relation to the realization of Green Accounting. Analysis of the application of environmental accounting to benchmark whether the Green Accounting entity is realized or not.This research is a qualitative descriptive study. The analysis was conducted by conducting in-depth interviews with the relevant parties as well as observing the environmental accounting, analyzing the BUMDes financial statements, and documenting the results. Data obtained through interviews, observation, and documentation. The data that has been obtained is then documented and drawn conclusions. The results showed that in accordance with PSAK 1 concerning the presentation of financial reporting, BUMDes "X" has compiled reports relating to environmental impacts. Although the report is still simple, the separate presentation of this environmental accounting report has shown concern for BUMDes "X" in providing information related to environmental accounting. Optimization of the application of environmental accounting ultimately depends on the policy, human resources, and infrastructure readiness of the implementing entity. . Keywords: environmental accounting, green accounting, environmental costs, financial statement, social responsibility